Peran Kegiatan Komersial dalam membentuk Sense of Place di Ruang Publik berdasarkan Persepsi Pengunjung (Studi Kasus: Taman Literasi, Blok M) - Chintya Primadinda Safira; Nurhikmah Budi Hartanti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the role of commercial activities in shaping the sense of place in Martha Christina Tiahahu Literacy Park, Blok M, Jakarta, a revitalized public space that has evolved into a multifunctional urban destination. The increasing presence of cafés, restaurants, bazaars, and promotional events has transformed the park by integrating social, recreational, and economic functions. A quantitative approach was employed using a survey of 100 visitors selected through purposive sampling. Sense of place was analyzed through three dimensions: place identity, place attachment, and place dependence, while commercial activities were assessed based on physical, activity, and meaning aspects. Data were analyzed descriptively and supported by correlation analysis. The findings indicate that commercial activities have a positive and significant relationship with all dimensions of sense of place. The strongest correlation was found with place dependence (r = 0.68), indicating that commercial facilities enhance functional comfort, convenience, and the perceived irreplaceability of the park. Commercial activities also show a moderate-to-strong relationship with place attachment (r = 0.59), reflecting the role of repeated social interactions and shared experiences in fostering emotional bonds. Meanwhile, place identity demonstrates a positive correlation (r = 0.53), suggesting that the integration of commercial elements increases spatial attractiveness, activity diversity, and functional completeness. Overall, the study concludes that proportionally managed commercial activities can enhance the quality and vitality of public spaces without undermining their social and cultural values. These findings emphasize the importance of balancing economic, social, and educational functions in the planning and management of contemporary urban public spaces.